Rebalancing EU Interest Representation? Associative Democracy and EU Funding of Civil Society Organizations1. (14th November 2013) - Sanchez Salgado, Rosa
Abstract European Union (EU) funding of civil society organizations (CSOs) is a substantial and important part of EU governance, but study of such funding is scarce and theoretically underdeveloped. To fill this gap, this article analyzes the main features of EU funding of CSOs and its effects on the EU system of interest representation, drawing on policy documents and the EU register of interest representatives. The resulting analysis shows that EU funding of CSOs in the social sector tends to reflect many of the characteristics of the model of associative democracy. European funds are being directed to groups that voice the concerns of excluded groups and, in this way, address imbalances in EU interest representation. The EU also promotes certain healthy features among CSOs, since it restricts access to funding opportunities to interest groups fulfilling key normative criteria. Hence, the EU helps sustain, but does not significantly constrain, the development of European CSOs.